Reverse Leakage Analysis for As-Grown and Regrown Vertical GaN-on-GaN Schottky Barrier Diodes - Kai Fu (IEEE Journal of the Electron Devices Society, 2020)
Vertical GaN-on-GaN Schottky barrier diodes based on as-grown and regrown samples were fabricated to investigate the effects of the etch-then-regrow process on device performance. The surface roughness increased slightly after dry etching and decreased after regrowth. According to X-ray diffraction results, the etch-then-regrow process caused a slight increase of defect density due to increased edge dislocations. Schottky parameters extracted from forward current-voltage curves, such as turn-on voltages of 0.74 V and 0.72 V, ideality factors of 1.07 and 1.10, and barrier heights of 1.07 eV and 1.05 eV, were obtained for diodes based on the regrown and as-grown samples, respectively. The breakdown voltage of the regrown sample was much lower than the as-grown sample. The regrowth interface can be regarded as a n-doping GaN layer due to the high interface charge density after the etch-then-regrown process. This equivalent n-doping GaN layer reduced the effective thickness of the UID-GaN under the Schottky contact thus causing lower breakdown voltage for the regrown sample. Poole-Frenkel emission and trap-assisted tunneling processes were responsible for the leakage of both as-grown and regrown samples according to the temperature dependence of the reverse currents.